The Social Organization of Education Research in England - Lawn, Martin; Furlong, John (European Educational Research Journal, 2007)
The field of education has grown enormously in England over the last 25 years in size, complexity, forms of production and purpose. It has been shaped by governmental, marketand production changes, and it appears to be moving outside the university sector as well. The British Educational Research Association is trying to map the field and to make sense of its development. This article begins with a search for relevant data about the key elements in the field- personne, institutions, output, etc.- and tries to draw conclusion about the next steps in this inquiry.
Keywords: Grande Bretagne; utilisation des recherches